Screen time, physical activity and BMI status among secondary students in Kuala Selangor / Siti Norazwani Pak Rudin - Pak Rudin, Siti Norazwani (2016)
Excessive screen times has been associated with displacements of physical activity among adolescents in this new developing advanced technologies as adolescents are exposed to various types of media electronics that can be assessed widely. Engagement with sedentary based media caused higher screen time thus exceeding the recommendation of two hours of screen time per daily basis thus cause physical inactivity among adolescents that give rise to obesity and increased risk of cardiovascular disease .This study then is designed in order to answer a few of research questions in terms of (1) time spent for the screen time activity by the secondary students in Kuala Selangor District (2) level of physical activity among secondary students in Kuala Selangor District and (3) association between total screen time, level of physical activity and BMI status of adolescents. A total of 291 students of 14 and 16 years old from two schools of Puncak Alam in area of Kuala Selangor had been adopted in this study. The instruments used was the self-administered questionnaires of screen times in which consisted of questions about viewing and usage of television, video games, computers, iPad or tablets and smartphones at home. Physical activity of adolescents was assessed by using Physical Activity Questionnaires for Adolescents. The students from three classes of Form Two and Form Four were selected randomly. The data of this study was analyzed by using Statistical Package for Social Science (SPSS) version 21.0. The mean BMI of students was 21.18 ± 4.99. Result shows the mean of total screen time during weekdays among male and female which is 431.16 ± 261.96 and 414.95± 245.47 respectively while during weekend, 689.53 ± 408.94 and 611.15 ± 346.38 respectively. Physical activity score for male is 2.9 ± 0.7 while for female is 2.2 ± 0.57. Apart from that, this study also outlines of significance difference between physical activity score with gender (p=.000) and no association of physical activity score and age group (p=0.067). There is also no association between total screen times and physical activity level. Weekdays (p=0.837) and weekend (p=0.774). There was also no association between BMI and screen times (weekdays and weekend) as well as physical activity, p= 0.776, 0.553 and 0.139 respectively.